2003
DOI: 10.1177/152660280301000503
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Dynamics during Head Movements: A Reason for Concern with Regard to Carotid Stenting?

Abstract: Following carotid stenting, sharp ICA angulation that are aggravated by forward bending of the head occur at the distal stent junction. The stented section of the carotid artery shows complete lack of flexibility despite highly flexible features of hte stents ex vivo. Both the CCA and ICA are subjected to considerable torsion shear with the head turned left and right. This shear is not accommodated by the current stent designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…This decision was motivated by an interest in investigating repeated loading events of the lesion such as pre-stenting expansion by a balloon, stenting followed by poststenting balloon expansion; as well as the effects of physiological loading of the lesion post-stenting due to movement. 38,45 The stress-strain response on unloading could have been used for the fit of f ¥ and i instead which would be of greater benefit to FE models in which only one loading-unloading cycle was present. Regardless the proposed model is more appropriate than the assumption of elasticity in determining the unloading behavior of the plaque, particularly as stress softening phenomena observed during the first unloading cycle were more significant than hysteresis effects in subsequent loading and unloading cycles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This decision was motivated by an interest in investigating repeated loading events of the lesion such as pre-stenting expansion by a balloon, stenting followed by poststenting balloon expansion; as well as the effects of physiological loading of the lesion post-stenting due to movement. 38,45 The stress-strain response on unloading could have been used for the fit of f ¥ and i instead which would be of greater benefit to FE models in which only one loading-unloading cycle was present. Regardless the proposed model is more appropriate than the assumption of elasticity in determining the unloading behavior of the plaque, particularly as stress softening phenomena observed during the first unloading cycle were more significant than hysteresis effects in subsequent loading and unloading cycles.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of stenting procedures where pre-or post-expansion is used the loading mechanism on the tissue will be similar in each loading phase allowing models of inelasticity similar to that proposed here to be used. For models that include different loading regimes such as bending or torsion that occur in peripheral arteries 45 an anisotropic inelastic model would need to be implemented. 13 The loading behavior defined by Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Also, since the disease itself may influence the magnitude and pattern of posture-related geometric alterations, future data should also include geometric changes due to head rotation in the setting of advanced disease. Stent implantation in carotid arteries is not common, but it is performed in about 20-30% of patients when endarterectomy is not possible such as in patients with highly calcified lesions or in carotids with complicated geometries [24]. Previous studies such as those by Valibhoy et al [25] and Diehm et al [26] have reported that carotid stents fracture in some occasions.…”
Section: Discussionmentioning
confidence: 99%
“…A parallel imaging technique (SENSE factor 2) was employed to reduce acquisition time. Variable flip angle (16)(17)(18)(19)(20)(21)(22)(23)(24) • ) and gradient first moment nulling techniques were applied to decrease saturation effects of inflowing blood and reduce signal loss due to complex flow, respectively. Each subject was imaged in two different scanning sessions on the same day corresponding to the two head postures examined: 1) a neutral head posture with the subject in the supine position; and 2) a rightward head rotation posture with the subject in the prone position.…”
Section: B Mrimentioning
confidence: 99%
“…The proposed hypothetical mechanism for this phenomenon is that head rotation ispilateral to the stenotic ICA applies significant axial, radial, and torsion shear forces on the affected critically stenotic ICA. 8,9 It has become almost conventional to consider a diagnosis of positional vertebrobasilar ischemia in patients presenting with symptoms specifically associated with lateral neck rotation or extension. 10,11 However, the positional carotid artery occlusion appears to be rare, and the pathological mechanism is not clear.…”
Section: Discussionmentioning
confidence: 99%